1979
DOI: 10.2134/agronj1979.00021962007100010004x
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Application of P. I. Screening of Various Inorganic and Organic P Compounds1

Abstract: The suitability of 32 different P compounds for foliar application was tested by using a new technique in which predetermined quantities of P were applied to a fixed leaf area. This made it possible to obtain quantitative data on absorption of added P and on translocation of absorbed P out of the treated area. Presently foliar applications of P are used less than N, one reason being that no P compound is available which can be sprayed on plants in large enough quantities without damaging the leaves. Several re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…A large number of P compounds were applied to maize and soybean leaves, to determine the maximum amount that could be applied without damage to the leaves Black 1979a, 1979b). In the first of two studies 32 different foliar P compounds were tested (Barel and Black 1979a). The most successful compound tested on maize was ammonium tripolyphosphate followed by ammonium polyphosphate and phosphoryl triamide.…”
Section: Phosphorus Rate and Foliar Scorchmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of P compounds were applied to maize and soybean leaves, to determine the maximum amount that could be applied without damage to the leaves Black 1979a, 1979b). In the first of two studies 32 different foliar P compounds were tested (Barel and Black 1979a). The most successful compound tested on maize was ammonium tripolyphosphate followed by ammonium polyphosphate and phosphoryl triamide.…”
Section: Phosphorus Rate and Foliar Scorchmentioning
confidence: 99%
“…Silbertstein and Wittwer 1951;Garcia and Hanway 1976;Gray 1977;Alston 1979;Barel and Black 1979a;Parker and Boswell 1980;Harder et al 1982;Mallarino et al 2001;Ahmed et al 2006). These studies demonstrated that the salt load, pH and nutrient mixture all had important effects on the efficacy of foliar P fertiliser.…”
Section: Introductionmentioning
confidence: 99%
“…Barel and Black (1979a) found that ammonium salts of orthophosphate dried rapidly and left dry crystals on the surface of the leaf, which depending on moisture availability and conditions such as temperature and humidity might be taken up later or washed away. In moist conditions, potassium phosphate is rapidly absorbed by leaf.…”
Section: Phosphorus-use Efficiencymentioning
confidence: 99%
“…To assay to the degree of foliar absorption, most studies utilize either rooted cuttings (9,10), seedlings (2,4,5,6,8) or excised leaves or discs to minimize space required for treatment (1,3,11). It is essential that the model system utilized reflects results that would be obtained by intact plants under actual practical application conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been employed including removal of the treated area (2,9,10), and rinsing or soaking in water (3,5,6,11), dilute acids and ions for exchange (4,6,7,6,12), or detergent solutions (1,12). Since many studies on foliar absorption require use of radioactive nutrients, many of these methods are undesirable due to personal safety and the increasing cost for disposal of large volumes of radioactive wastes.…”
Section: Introductionmentioning
confidence: 99%